2009
DOI: 10.1002/eat.20665
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and evaluation of the Clinical Impairment Assessment to assess disordered eating related distress in an adolescent female ethnic Fijian population

Abstract: Objective:Measurement of disease-related impairment and distress is central to diagnostic, therapeutic, and health policy considerations for eating disorders across diverse populations. This study evaluates psychometric properties of a translated and adapted version of the Clinical Impairment Assessment (CIA) in an ethnic Fijian population.Method:The adapted CIA was administered to ethnic Fijian adolescent schoolgirls (N = 215). We calculated Cronbach's α to assess the internal consistency, examined the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 18 publications
3
35
1
1
Order By: Relevance
“…We evaluated herbal purgative use as a potential LPA indicator with the following item incorporated into the EDE-Q: “Over the past 28 days, how many times have you taken traditional Fijian dranu to cause diarrhea, clean out your stomach, or suppress your appetite as a means of controlling your shape or weight?” We have previously reported that self-reported herbal purgative use was prevalent in our sample, and significantly associated with both eating pathology (Becker et al , 2009c) and eating-related clinical impairment (Becker et al , 2009b). …”
Section: Methodsmentioning
confidence: 77%
See 3 more Smart Citations
“…We evaluated herbal purgative use as a potential LPA indicator with the following item incorporated into the EDE-Q: “Over the past 28 days, how many times have you taken traditional Fijian dranu to cause diarrhea, clean out your stomach, or suppress your appetite as a means of controlling your shape or weight?” We have previously reported that self-reported herbal purgative use was prevalent in our sample, and significantly associated with both eating pathology (Becker et al , 2009c) and eating-related clinical impairment (Becker et al , 2009b). …”
Section: Methodsmentioning
confidence: 77%
“…The study utilized data originally collected as part of a two-stage design described previously (Becker et al , 2009b; Becker et al , 2009c). Briefly, all participants completed a self-report battery at Stage 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these recognizable features as potential consequences of globalization, Becker et al recently found that 35% of Fijian school girls ages 15 to 20 years endorsed traditional herbal purgative use. 56 Follow-up analyses indicated that traditional herbal purgative use was associated with significantly elevated impairment and distress in these girls, 57 supporting the value of culture-specific assessments to enhance detection of eating disorder symptoms in non-Western contexts. 56 However, Becker 54 cautioned that syndromes identified within a Western context may not be represented in a comparable indigenous illness category.…”
Section: Who Most Likely Presents With Purging Disorder?mentioning
confidence: 88%